A Study of Feminine Accounting in Household Financial Management Practices: A Case Study of Housewives in RT 005 RW 006, Kelurahan Gumuruh - Kodariah, Siti; Riansyah Putra, Ricky; Noor, H. Qur'ani; Sukmana, Sina Delphia (Greenation Research & Yayasan Global Resarch National, 2024)
This research aims to explore the adaptation of feminine accounting in household financial management practices among housewives in RT 005 RW 006 Kelurahan Gumuruh. A qualitative approach using case study methods was employed to understand how feminine accounting can create a more inclusive and gender-responsive financial management system. Data were collected through interviews, observations, and document analysis. The results show that feminine accounting enables more equitable and gender-sensitive household financial management. Additionally, the adaptation of feminine accounting supports family welfare by enhancing women's participation in financial decision-making. This study recommends training and education on feminine accounting to strengthen housewives' roles in effectively managing family finances.